Position Estimate Localization Routing for Large Scale Wireless Sensor Networks - Rastogi, Shishir; Rastogi, Neeta; Darbari, Manuj (International Journal of Computer Sciences and Engineering, 2019)
Localization is a significant characteristic in Wireless Sensor Networks (WSNs) area, and it has much research concentration between academia and the research community. WSN is designed and implemented using a vast number of tiny, low energy, limited processing capability and low-cost sensors interconnected wirelessly in an ad-hoc manner. The concept of describing physical coordinates, i.e. the location of sensor nodes in WSNs is a major issue in communication systems to assess the point of origin of events under monitoring. The necessity of the positioning accuracy differs for different applications so different approaches for localization are utilized in various applications. WSNs use two different type of localization methods, Range based and Range-free. Range based localization is expensive and used for accurate position estimation in positioncritical applications like forest fire detection, reconnaissance etc. whereas Range-free localization is much economic and used for ascertaining approximate position estimation in not-so-position-critical applications like livestock and animal tracking etc. In this paper, an efficient recursive localization method called Position Estimate Localization Routing (PELR) is proposed for range-free localization. It reduces the consumption of energy, the time of execution, and the communication overhead. It enhances overall system performance for large-scale WSNs taking into consideration the trade-off between location accuracy and time cost. The simulation outcomes demonstrate that the recommended system has enhanced performance than the existing ones.